(untitled) (Bangladesh Agronomy Journal, 2015)
A field experiment was conducted at the experimental field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during November 2012 to March 2013 to evaluate the response of three (3) wheat varieties viz., BARI Gom23, BARI Gom24 and BARI Gom25 under four levels of nitrogen fertilizer i.e, 75, 100, 125 and 150 kg N ha-1. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Results showed that plant height, number of leaves plant-1, leaf length and dry matter content were significantly affected due to varieties and/or nitrogen levels. Grains ear-1, number of fertile grains plant-1, 1000-grain weight, grain yield and harvest index were also significantly influenced by varieties and/or nitrogen levels. The value of all parameters studied in this experiment increased with increasing nitrogen levels up to 125 kg N ha-1 and thereafter decreased with fertilizer increasing level. Combination results showed that BARI Gom-24 with application of 125 kg N ha-1 gave the maximum grain yield (4.71 t ha-1), harvest index (49.37 %) and protein content (10.88%). Bangladesh Agron. J. 2015, 18(1): 89-98